Scolecohyalosporium thailandense sp. nov. (Parabambusicolaceae, Pleosporales) collected on Imperata sp. (Poaceae) in northern Thailand - Phookamsak, Rungtiwa; Hongsanan, Sinang; Bhat, Darbhe Jayarama; Xu, Jianchu; Mortimer, Peter E.; Suwannarach, Nakarin; Kumla, Jaturong; Dawoud, Turki M.; Lumyong, Saisamorn (Phytotaxa, 2023)
In the present study, a new species, Scolecohyalosporium thailandense, is introduced based on morphological and molecular approaches. The species was found as a saprobe occurring on Imperata sp. (Poaceae) in terrestrial habitats in Chiang Rai Province, Thailand. This species is characterized by solitary, semi-immersed to erumpent, subglobose to ampulliform, papillate ascomata, dark brown pseudoparenchymatous peridium, fissitunicate, cylindrical to subcylindrical asci embedded in a hyaline, filamentous to cellular pseudoparaphysate hamathecium, and filiform, yellowish, septate ascospores. Phylogenetic analyses based on a concatenated ITS, LSU, SSU, and TEF1-α sequence matrix demonstrated that S. thailandense formed a well-resolved clade with S. submersum (the type species of this genus) and Scolecohyalosporium sp. within the Parabambusicolaceae. Therefore, S. thailandense is introduced herein as the second species of the genus Scolecohyalosporium. Morphological characteristics, illustrations, and updated phylogenetic analyses are provided, and notes on species distinctiveness with closely related taxa are discussed.